Ib期上叶肺癌纵隔淋巴结清扫方式的研究 (Zhongguo Fei Ai Za Zhi, 2013)
BACKGROUND AND OBJECTIVE: Lymphatic metastasis is the most important way for the spread of lung cancer and is one of the important factors affecting the prognosis. Existing studies showed that compared to middle or lower lobe NSCLC, upper lobe non-small cell lung cancer (NSCLC) has a higher probability of occurring regional mediastinal lymph node metastasis. The purpose of this study is to research the prognostic factors and lymphadenectomy of stage Ib upper lobe NSCLC. METHODS: A retrospective study of 147 consecutive subjects (76 and 71 for right and left upper lobe NSCLC respectively) who had undergone curative resection for stage Ib upper lobe NSCLC was performed. A total of 925 lymph nodes were removed during the surgery in all enrolled patients and a total of 491 mediastinal lymph nodes (266 and 225 for superior and inferior mediastinal lymph nodes respectively) were removed. Kaplan-Meier product method and Log-rank test were used for univariate survival analysis and Cox regression model was used for multivariate survival analysis. RESULTS: ① Both univariate and multivariate analysis showed that age, tumor size and number of removed superior mediastinal lymph node stations were the important prognostic factors of stage Ib upper lobe NSCLC; ②For stage Ib right upper lobe NSCLC, station 4 lymph node was of statistical significance to the prognosis (P=0.021); while for stage Ib left upper lobe NSCLC, station 5 lymph node was of statistical significance to the prognosis (P=0.024). CONCLUSION: In surgically treated stage Ib upper lobe NSCLC patients, age, tumor size and number of removed superior mediastinal lymph node stations are the important prognostic factors. And in this kind of patients, lobe-specific systematic lymph node dissection may be a more efficient procedure during the surgery.